The Productivity Improvement and Population Growth of Payakumbuh Duck (Anas platyrhynchos domestication) Using a Simple Aspirator Tool on Artificial Insemination (AI) Technology - Tertia Delia Nova; Suhartati Suhartati; Azhar Azhar (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2022)
This study aimed to determine the effect of IB frequency using different simple aspirator on fertility, weight loss and hatchability of Payakumbuh duck (Anas platyrhynchos domestication) eggs. This study used 8 male and 20 female ducks, 90% egg production. In this study, all hatched the hatched eggs. This study used an experimental method with a completely randomized design (CRD) with 4 treatments and 5 replications. The treatments consisted of: P1 is 1 x 2 days, P2 is 1 x 4 days, P3 is 1 x 6 days, P4 is 1 x 8 days; the parameters observed were fertility, weight loss and hatchability. The results of the analysis of variance showed that different AI frequencies had a significant effect (P < 0.05) on the fertility of hatching eggs, but had no significant effect (P > 0.05) on weight loss and hatchability. It can be concluded that P2 had a significant effect (P < 0.05) on fertility because fertile eggs were higher than other treatments. The characteristics of Payakumbuh ducks (Anas platyrhynchos domestication) spermatozoa are milky white and yellowish white, thick and watery consistency, specific odor, volume 0.24±0.05 ml, pH 7.37±0.51, mass movement +, ++ and +++, live percentage 79.06±3.68%, concentration 2.342 billion cells/ml, motility 75.00±7.56% and abnormality 12.06±0.82%. The results of the analysis of variance showed that different AI frequencies had a significant effect (P < 0.05) on the fertility of hatching eggs, but had no significant effect (P > 0.05) on weight loss and hatchability. The frequency of IB 1 x 4 days had the highest fertility rate, namely 67.72 ± 7.99%. A simple Aspirator can function properly with the need for repairs and upgrades in several parts of the tool such as current source, and fan capacity.